Software design and development for a direction of arrival estimation system - Xiao, Yi (2009)
Nowadays, radar system has been widely used in many applications, such as navigation and positioning at sea, measuring distances and map geographical areas, monitoring of precipitation by meteorologists, scientific study and for defense by using various radar tracking and surveillance systems, etc. In this project, the student used LabVIEW (Laboratory Virtual Instrumentation Engineering Workbench), a platform and development environment for visual programming language from National Instruments, to design and develop a system for Direction of Arrival (DOA) estimation. A signal source emitter and a receiver were set up to analyze the direction of the signal source. The student used oscilloscope as part of the radar system receiver and processed the data with a specific algorithm to figure out the direction of the incoming signal source. By using LABVIEW, the student created a GUI (graphical user interface) to control the oscilloscope through a computer using USB port connection and thus the data can be acquired from the computer in desired format. The simulation of Direction of Arrival using LabVIEW also discussed in this project.